Proposta de segmentação de passageiros segundo a métrica de consumo em aeroportos - Côrtes, Marina Rodine (2019)
With the recent changes in the Brazilian airspace, the airport demand has been more and more frequent and diverse; however, terminals are not following this new reality with the same effort, which results in long queues, reduction of the level of service and, consequently, commercial revenues with values lower than international standards. An option to potentialize these revenues is try to provide a better environment, service and strategies so that the passengers can feel more comfortable with the act of consume. However, to make this happen, it is necessary to understand their inclination to purchases and the main factors that has influence on this behavior. Thus, this work aims to assist airport managers proposing a passenger segmentation model based on their intrinsic characteristics and on the provocations that they suffer when coming into contact with the airport environment. The main product of this research emerges from the fusion of the classifications of these two main elements, which results in six key passenger segments. This model can be adapted to different contexts, through consultation with local experts. Besides the threading model itself and profiles resulted from this segmentation, the study also presents an expert consultation (in order to exemplify the work to be done by the managers) and some methods of data capture (to be used according to the availability of resources at each airport).